Rare thrombotic complications as an initial presentation of nephrotic syndrome - Suvarna V Rajput,; Vishal Sawant,; Kiran Sathe,; Alpana S Kondekar, (Indian Journal of Child Health, 2021)
Thrombosis in nephrotic syndrome (NS) is rare event with approximate incidence being 2–3%. Mostly these complications follow NS with involvement of superficial and deep venous system. Cerebral venous sinus thrombosis (CVST) as an initial presentation of NS is rarely reported. Here, we described two cases; an 8-year-old boy and 9-year-old girl, who developed life threatening CVST and renal vein thrombosis, respectively, as initial presentation of NS. Both cases were diagnosed with early imaging studies and treated with appropriate anticoagulant therapy with complete resolution on repeat imaging.